Factors influencing the uptake of household water connections in peri-urban Maputo, Mozambique - Jimenez-Redal, Ruben; Parker, Alison; Jeffrey, Paul (Elsevier Science B.V., Amsterdam., 2014)
Rapid urbanization in many African cities has had a significant impact on the basic water services in peri-urban areas, where providing services can be complex. In the city of Maputo, Mozambique, the initial uptake of new household connections following network construction in peri-urban areas was slow. Focus group discussions with residents and interviews with key actors revealed the importance of offering flexible payment options to the urban poor in order to increase the affordability of connection charges. Although the high connection fee was a constraint, residents were willing to pay if the charges were spread across several monthly installments. These findings suggest that flexible payment arrangements for customers can both bring utility services within reach of low income households and expand the customer base for utility service providers.
Keywords: Household connections; Water supply; Peri-urban areas; Mozambique